Analysis of Entreprenuership Knowledge on Entrepreneurial Interest of Tadris Biology Student - Hotmaidah Hasibuan (Institut Agama Islam Negeri, 2023)
Entrepreneurship is the process of identifying, developing and implementing a vision. This vision can take the form of innovative ideas and sales ideas. Unemployment is a big problem in Indonesia that is still difficult to overcome because the rapid population growth is not matched by an increase in job opportunities. Companies are becoming more selective in recruiting new employees, but interest in entrepreneurship among Indonesia's young generation is still relatively low. In situations like this, the world of education has a responsibility to increase the interest of the younger generation in entrepreneurship. The increasing number of graduates will increase competition in looking for work and the lack of job opportunities will increase the number of unemployed. Being unemployed is something that many people don't want because apart from being detrimental to themselves, it is also not good for the community around them. The aim of this research is to determine the importance of entrepreneurship courses for biology study program students. This study uses a qualitative method. The data collection techniques are observation, interviews and documentation. The presence of entrepreneurship courses in universities can foster entrepreneurship by instilling knowledge and interest in entrepreneurship, increasing self-confidence and entrepreneurial skills, as well as increasing motivation to become a young entrepreneur.